2014
DOI: 10.1088/0004-637x/797/2/111
|View full text |Cite
|
Sign up to set email alerts
|

NuSTAROBSERVATIONS AND BROADBAND SPECTRAL ENERGY DISTRIBUTION MODELING OF THE MILLISECOND PULSAR BINARY PSR J1023+0038

Abstract: We report the first hard X-ray (3-79 keV) observations of the millisecond pulsar (MSP) binary PSR J1023+0038 using NuSTAR. This system has been shown transiting between a low-mass X-ray binary (LMXB) state and a rotation-powered MSP state. The NuSTAR observations were taken in both LMXB state and rotation-powered state. The source is clearly seen in both states up to ∼ 79 keV. During the LMXB state, the 3-79 keV flux is about a factor of 10 higher that in the rotation-powered state. The hard X-rays show clear … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 33 publications
2
51
1
Order By: Relevance
“…Although the folded X-ray lightcurve does not cover a full orbital cycle, the X-ray variation is likely periodic with an X-ray minimum around the inferior conjunction (Figure 1b). A similar phenomenon has been previously seen in the RB PSR J1023+0038 (Bogdanov et al 2011;Tendulkar et al 2014;Li et al 2014). From the Chandra data bins, the X-ray maximum occurs around the superior conjunction (i.e., φ 20 ∼ 0.5; observer-pulsarcompanion), although the Swift data favours the flux maximum around φ 20 > 0.5.…”
Section: Possible X-ray Orbital Modulationsupporting
confidence: 83%
See 2 more Smart Citations
“…Although the folded X-ray lightcurve does not cover a full orbital cycle, the X-ray variation is likely periodic with an X-ray minimum around the inferior conjunction (Figure 1b). A similar phenomenon has been previously seen in the RB PSR J1023+0038 (Bogdanov et al 2011;Tendulkar et al 2014;Li et al 2014). From the Chandra data bins, the X-ray maximum occurs around the superior conjunction (i.e., φ 20 ∼ 0.5; observer-pulsarcompanion), although the Swift data favours the flux maximum around φ 20 > 0.5.…”
Section: Possible X-ray Orbital Modulationsupporting
confidence: 83%
“…A few RBs, known as transitional MSPs, have already shown remarkable transition(s) between the LMXB state and the radio pulsar state in optical, X-rays, and/or γ-rays (i.e., M28I; Papitto et al 2013, PSR J1023+0038; Archibald et al 2009;Patruno et al 2014, and PSR J1227−4853; Roy et al 2015), clearly indicating the close relationship between LMXBs and radio MSPs. BW/RBs are interesting objects, not to mention the fascinating theoretical interpretation of multi-wavelength observations for individual studies (e.g., the keV-to-GeV emission models of PSR J1023+0038 in different states; Li et al 2014;Papitto & Torres 2015). They also pro-vide crucial information on the long-term accretion history.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We do not find evidence for orbital modulation of the X-ray brightness during any of the three modes. Li et al (2014a) have reported evidence for periodicity at 3130 s in the NuSTAR data set of PSR J1023+0038. We have examined both XMM-Newton observations in search of a similar signal but find no evidence for it.…”
Section: X-ray Variabilitymentioning
confidence: 98%
“…The J1023+0038 pulsar provides a useful test bed at a distance of 1.37 kpc toward the γ-ray source 2FGLJ1023.6+0040: an accretion disc was observed in the optical in 2000-2001; the detection of radio pulses from a MSP followed in 2007, until the pulses disappeared in 2013, quenched or eclipsed by the ionized flow from a new X-ray accretion disc [97,98,99]. The interaction between the pulsar magnetosphere/wind and the accretion disc is very dynamic, switching between different spectral states in X rays, with and without orbital modulation [98], and producing radio continuum emission and sporadic flares in the optical, UV, and X-rays, suggestive of propellor modes [97]. The γ-ray flux quintupled when the radio pulses disappeared [69,100].…”
mentioning
confidence: 99%